Study of the history of foreign European and American countries of modern and contemporary at the History Department - Миколенко, Д. В. (The Journal of V. N. Karazin Kharkiv National University. Series History, 2015)
The article analyzes the main research directions of Modern and Contemporary History of foreign countries in Europe and America that are presented at the History Department. The author identifies the factors that have caused the most priority scientific investigation themes of the employees and reveals the strategic tasks of the successive development of novistik.